The possible roles of hyperpolarization-activated cyclic nucleotide channels in regulating pacemaker activity in colonic interstitial cells of Cajal - Shahi, Pawan Kumar (Springer Japan, 2013)
BACKGROUND: Hyperpolarization-activated cyclic nucleotide (HCN) channels are pacemaker channels that regulate heart rate and neuronal rhythm in spontaneously active cardiac and neuronal cells. Interstitial cells of Cajal (ICCs) are also spontaneously active pacemaker cells in the gastrointestinal tract. Here, we investigated the existence of HCN channel and its role on pacemaker activity in colonic ICCs. METHODS: We performed whole-cell patch clamp, RT-PCR, and Ca(2+)-imaging in cultured ICCs from mouse mid colon. RESULTS: SQ-22536 and dideoxyadenosine (adenylate cyclase inhibitors) decreased the frequency of pacemaker potentials, whereas both rolipram (cAMP-specific phosphodiesterase inhibitor) and cell-permeable 8-bromo-cAMP increased the frequency of pacemaker potentials. CsCl, ZD7288, zatebradine, clonidine (HCN channel blockers), and genistein (a tyrosine kinase inhibitor) suppressed the pacemaker activity. RT-PCR revealed expression of HCN1 and HCN3 channels in c-kit and Ano1 positive colonic ICCs. In recordings of spontaneous intracellular Ca(2+) [Ca(2+)](i) oscillations, rolipram and 8-bromo-cAMP increased [Ca(2+)](i) oscillations, whereas SQ-22536, CsCl, ZD7288, and genistein decreased [Ca(2+)](i) oscillations. CONCLUSIONS: HCN channels in colonic ICCs are tonically activated by basal cAMP production and participate in regulation of pacemaking activity.